266 Deformation imaging by strain in chronic heart failure over sacubitril–valsartan: a multicentre echocardiographic registry (discover)—ARNI. (8th December 2021) - Mandoli, Giulia Elena; Pastore, Maria Concetta; Giannoni, Alberto; Benfari, Giovanni; Dini, Frank Lloyd; Rosa, Gianmarco; Pugliese, Nicola Riccardo; Taddei, Claudia; Correale, Michele; Brunetti, Natale Daniele; Mazzeo, Pietro; Carluccio, Erberto; et al.
Abstract: Aims: Sacubitril/valsartan have changed the treatment of heart failure with reduced ejection fraction (HFrEF), due to the positive effects morbidity and mortality partly mediated by left ventricular reverse remodelling (LVRR). The aim of this multicentre study was to identify echocardiographic predictors of LVRR after sacubitril/valsartan administration. Methods and results: Patients with HFrEF requiring therapy with sacubitril/valsartan from 13 Italian centres were included. Echocardiographic indexes including speckle tracking echocardiography (STE) indexes were used to predict LVRR [defined as LV end-systolic volume reduction and ejection fraction (LVEF) improvement > 10% at follow-up] at 6 months follow-up as the primary endpoint. Changes in symptoms (NYHA class) and neurohormonal activations [N-terminal-pro-brain natriuretic peptide (NTproBNP)] were also evaluated as secondary endpoints. The final population (excluding patients with poor acoustic windows and missing data) consists of 341 patients [mean age: 65 ± 10 years; 18% female, median LVEF 30% (interquartile range: 25–34)]. At 6 months follow-up, 82 (24%) patients showed early complete response (LVRR and LVEF ≥35%), 55 (16%) early incomplete response (LVRR and LVEF <35%), 204 (60%) no response (no LVRR and LVEF <35%). Non-ischaemic etiology, a lower left atrial volume index and a higher global longitudinal strain were all independent predictors of LVRR at multivariable logistic analysis (all P < 0.01). LA strain was the best predictor of positive changes in NYHA class and NT-proBNP (all P < 0.05) (Figure 1). Conclusions: STE parameters at baseline could be useful to predict LVRR and clinical response to sacubitril-valsartan, and thus could be used as a guide for treatment in patients with HFrEF.